Information management in the operation of the civil engineering pavilion of a university in the Lima area – 2024 - Huaricallo Vilca, Yvan (2025)
The operation and maintenance of university buildings are facing accelerated deterioration due to a lack of preventive planning and information management, which affects the functionality and comfort of occupants. This research aims to determine the influence of information management on the operation of the Civil Engineering Pavilion of a university in Cercado de Lima. The research was basic, with a quantitative approach, a non-experimental design, and a descriptive-comparative scope. Structured questionnaires were administered to 145 students, 15 faculty members, and 6 administrative staff, and surveys were conducted with maintenance staff and the head of the General Services Office. The use of low-cost environmental sensors connected to an Arduino board was also integrated to measure physical variables such as temperature, humidity, CO2, and volatile compounds.The descriptive results showed dissatisfaction with thermal and acoustic comfort, as well as deficiencies in natural ventilation, especially from the perspective of students and faculty. These perceptions were supported by on-site measurements, where temperatures reached 29.3°C and humidity dropped to 63%, demonstrating thermal accumulation. From an institutional perspective, deficiencies were identified in maintenance planning and traceability, with informal communications and a lack of audits. In conclusion, it is demonstrated that information management and active occupant participation are key to an efficient and sustainable educational infrastructure, making it necessary to implement formal protocols, digital technologies, and continuous assessment mechanisms.